Detection of bone marrow involvement in newly diagnosed post-transplant lymphoproliferative disorder: 18F-fluorodeoxyglucose positron emission tomography/computed tomography versus bone marrow biopsy. Issue 10 (2nd October 2016) - Gheysens, Olivier; Thielemans, Sanne; Morscio, Julie; Boeckx, Nancy; Goffin, Karolien E.; Deroose, Christophe M.; Sagaert, Xavier; Wlodarska, Iwona; Verhoef, Gregor; Dierickx, Daan; Tousseyn, Thomas
Abstract: Detecting bone marrow involvement (BMI) in lymphoma is important as it adversely affects stage. Bone marrow biopsy (BMB) remains the standard to detect BMI but is prone to sampling error. We retrospectively investigated whether 18 F-fluorodeoxyglucose positron emission tomography with computed tomography ( 18 F-FDG-PET/CT) could identify BMI in patients with post-transplant lymphoproliferative disorder (PTLD) with sufficient accuracy in comparison with staging BMB. Twenty-five patients diagnosed with PTLD who underwent 18 F-FDG-PET/CT and BMB within one month were evaluated. Based on our criteria, six patients (24%) were considered positive for BMI on 18 F-FDG-PET/CT compared to one by BMB. Although we cannot completely exclude false positive results on 18 F-FDG-PET/CT, our data indicate a significantly higher sensitivity of 18 F-FDG-PET/CT compared to BMB (100% vs 17%) but similar specificity. These data confirm the high diagnostic performance of 18 F-FDG-PET/CT for detecting BMI, but prospective studies are needed to determine whether 18 F-FDG-PET/CT could indeed replace staging BMB in PTLD.